Practical aspects of using HRTF measuring device - Plaskota, Przemysław; Pruchnicki, P. (Archives of Acoustics, 2006)
Measurement of Head Related Transfer Function is complicated due to the object of the test, namely the transfer function of acoustical arrangement composed of pinna, head and torso. The test involving the participation of a person requires providing appropriate conditions for conducting measurement. Maintaining constant geometrical configuration of the sound source and the microphone placed in the ear’s channel is particularly important. Fulfilling this condition as well as determining the exact position of the sound source in relation to the measurement microphone may require application of a special measurement device. The paper presents the results of measuring HRTF function using special device. The problems encountered during the measuring process are discussed and the possible solutions are suggested. Finally, the results of the tests for a real human subject are presented in the paper.